Italy : Technical Note on the Financial Situation of Italian Households and Non-Financial Corporations and Risks to the Banking System. (IMF Staff Country Reports; Country Report, 2013)
This Technical Note examines the financial situation of Italian households and nonfinancial corporations and risks to the banking system. The credit risk from Italian households is mitigated by their considerable net wealth. Income has declined during the crisis, leading to tighter financial conditions for households, especially for young and low-income groups, but low indebtedness, high levels of assets, and declining interest rates have protected households from widespread debt payment difficulties. The financial situation of nonfinancial corporations, in particular small and medium-sized enterprises, is fragile, as evidenced by already high loan default rates. Continued strong policy action will be important to mitigate the impact of these vulnerabilities, especially for firms.